Relationship Between Teachers'Self-Efficacy Perceptions and Job Satisfaction Level - Karabiyik, Belkis; Korumaz, Mithat (ELSEVIER SCIENCE BV, 2014)
The aim of the study is to investigate the relationship between teachers' self-efficacy perceptions and job satisfaction level. Short Form Minnesota Satisfaction Questionaire and Self-efficacy Perception Instrument were used for the study. The sample of the study consists of 83 teachers of different branch and from different schools in Turkey. Descriptive statistics and Pearson Correlation statistics have been used to analyze the data in the study. According to the result, there is a significant and positive relationship between teachers' self-efficacy perceptions and job satisfaction level. (C) 2013 The Authors. Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Academic World Education and Research Center.
Keywords: Self-afficacy; Job satisfaction; SELF-EFFICACY; MOTIVATION; Education & Educational Research